Regional development of employment in eastern Germany. An analysis with an econometric analogue to shift-share techniques - Uwe Blien; Katja Wolf (European Regional Science Association (ERSA), 2002)
This paper examines the development of regional employment in eastern Germany. An approach introduced by Patterson and suggested by Möller/Tassinopoulos is extended for the analyses. This approach uses a generalisation of an econometric analogue of the common shift-share method, which is suggested here as a new "workhorse" for regional analyses. The results obtained with this "shift-share-regression" and with very differentiated data from the employment statistics of eastern Germany show that processes of deconcentration play a role in explaining regional disparities, since inverse localisation and positive urbanisation effects are visible. Such processes can be understood with approaches of "New Economic Geography" (based on Krugman et al.), whereas the general significance of industry-specific effects, which is also becoming clear, can be explained using approaches of structural change, following amongst others Appelbaum & Schettkat. In addition, positive impulses of the qualification structure on regional development are detectable, which can be understood by endogenous growth theory.
Keywords: 330